2020
DOI: 10.3389/feart.2020.552833
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Interpolation Model for Synthetic Aperture Radar Wind Retrieval

Abstract: The variational model inversion (VAR) method for synthetic aperture radar (SAR) wind retrieval based on the Bayesian theory can overcome the limitations of the traditional wind streak algorithm by introducing background wind and considering all sources of error, but its optimal solution is unstable and the time latency is long. In this article, we propose a new wind retrieval method by applying the optimal interpolation (OI) theory to construct a formula that considers the SAR information, background informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The WD inversion for the SAR image data is based on the wind streak features in the SAR data. Due to the complexity of the SAR imaging and the variability of the sea and air environment, not all of the SAR images contain clear wind streak features [118,119]. There are certain limitations in obtaining the WD with this method [64,120].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WD inversion for the SAR image data is based on the wind streak features in the SAR data. Due to the complexity of the SAR imaging and the variability of the sea and air environment, not all of the SAR images contain clear wind streak features [118,119]. There are certain limitations in obtaining the WD with this method [64,120].…”
Section: Discussionmentioning
confidence: 99%
“…In WS inversion, Jones et al used SEASAT SAR data and found that there was a certain relationship between the normalised radar cross-section (NRCS) of the SAR and WS [11]. Then, the geophysical model function (GMF) based on the NRCS of copolarized SAR was proposed and continually updated to form a series of empirical models [12,13]. However, the phenomenon of saturation exists in WS inversion with copolarized SAR when the WS exceeds 25 m/s [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy of LSTM may be compromised with the inclusion of exogenous features in the training sets and the duration of the prediction ahead. Back propagation (BP) [20][21][22][23] and improved particle swarm optimization (IPSO) [24][25][26][27] have been widely used in the wind energy resource evaluation, but the BP neural network (NN) has the shortcomings of a local minimization and a slow convergence speed. Combining the BPNN model with the PSO algorithm can effectively avoid the local optimal problem [28,29].…”
Section: Introductionmentioning
confidence: 99%